A Bayesian network to study motivation, motivational climate and anxiety in young competitive team players - Garcia-Mas, Alexandre; Fuster-Parra, Pilar; Ponseti, Francisco-Javier; Palou, Pere; Olmedilla, Aurelio; Cruz, Jaume (Anales de Psicología / Annals of Psychology, 2014)
The objective of this study is to find out the level of relations between self-determination, the goal orientation and the perceived motivational climate in young team players, and their impact on the somatic and cognitive components of the competitive anxiety, and the acceptance of use of cheating and gamemanship in sports. We adminstered the PMCSQ-2, TEOSQ, BRSQ, CDED and SAS-2 to a population of 270 soccer, handball and basketball players (M = 14.67 , SD = 1.53). Probabilistic relations of dependence and independence among the variables were established using a Bayesian network (BN) implemented with Netic and Tetrad IV. Subsequently, we instantiated hypothetical probability values ​​in the dependent variables of the BN to analyze the impact and change on the probabilities of the independent variables. Results showed that the causal impact of the self-determined motivation on the competitive anxiety is quite different from the achievement motivation; and also demonstrated a controversial relationship between the perceived motivational climates and the players’ goal orientations (task and ego). The marginal causal role of the somatic anxiety, and the instrumental role of the acceptation of the use of cheating were also confirmed. Results also confirmed the validation of the BN for this study.